Re-Homing and Identity Reconstruction of Diaspora in Jhumpa Lahiri’s “When Mr. Pirzada Came to Dine” - Moh Zaimil Alivin (Universitas Airlangga, 2021)
This study aims to analyse and describe how diaspora characters in “When Mr. Pirzada Came to Dine” reconstructed their identity and negotiate the process of re-homing in their current home. “When Mr. Pirzada Came to Dine” short story (WMPCD), written by Jhumpa Lahiri, depict the complex relation of identity and home experienced through diaspora characters, Pirzada and Lilia’s family. To pursue the objective of the study, qualitative descriptive approach was used together with Laurenson’ and Swingewood’s sociological criticism theory, Castells’ identity formation, and Zhang’s re-homing theory. The results of this study indicated that the process of re-homing depicted in WMPCD has a significant impact on the identity formation of diaspora characters, in this case, Pirzada and Lilia’s family. It means that the diaspora process of identity construction will not be efficiently completed since identity, particularly for diaspora individuals, will continue to be established and reconstructed in the context of the identity-forming resources accessible in their new ‘home’ and what they bring from their homeland. When it comes to re-homing and de-homing, the process of navigating this identification is becoming increasingly complex and sophisticated. ‘Home’ is no longer exclusively defined geographically as location, but by time and the people who contribute to forming personal ties to similar experiences. In short, re-homing becomes an essential element of the identity reconstruction process